A MINI REVIEW: STUDI KOMPUTASI TERHADAP STRUKTUR ELEKTROLIT PADA SILICENE, GRAPHENE, DAN GERMANENE - Harvina, Harvina; Gunawan, Rahmat; Allo, Veliyana Londong (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2024)
Research on two-dimensional (2D) materials such as graphene, silicene, and germanene has garnered significant attention due to their unique electronic and mechanical properties. This mini review employs Density Functional Theory (DFT) to compare the electronic properties of these three materials. The results show that graphene, with sp² hybridization, possesses outstanding electrical conductivity and high mechanical strength, with a lattice constant of 2.46 Å. Silicene and germanene, composed of silicon and germanium atoms respectively, exhibit higher surface reactivity and potential for advanced electronic applications due to their ability to open band gaps through various methods. Silicene has a lattice constant of 3.90 Å and an electronegativity of 1.9, while germanene has a lattice constant of 3.97 Å and an electronegativity of 2.01. The band structures of silicene and graphene do not exhibit band gaps, with dominant states in the p orbital, whereas germanene displays semiconductor behavior with a zero band gap opening at the K-point. Graphene shows high in-plane stiffness, while silicene and germanene have respective stiffness, with graphene and silicene being brittle and germanene being ductile. This study provides insights into the fundamental differences in the electronic properties of graphene, silicene, and germanene, as well as their potential applications in semiconductor technology and high-speed, low-energy electronic devices. Keywords: Silicene, Graphene, Germanene, DFT, Electronic structure